2016
DOI: 10.7554/elife.13053
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic protein interactions reveal a functional map of the cell

Abstract: To understand the function of eukaryotic cells, it is critical to understand the role of protein-protein interactions and protein localization. Currently, we do not know the importance of global protein localization nor do we understand to what extent the cell is permissive for new protein associations – a key requirement for the evolution of new protein functions. To answer this question, we fused every protein in the yeast Saccharomyces cerevisiae with a partner from each of the major cellular compartments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(60 citation statements)
references
References 41 publications
11
49
0
Order By: Relevance
“…In line with observations made by Berry et al (Berry, Olafsson et al 2016), the GrabFP components were in some cases themselves mislocalized due to interaction with target proteins. This was particularly relevant for GrabFP-A Ext and GrabFP-B Int (Figure 2 Figure Supplement 1H), which were, presumably as a consequence, less efficient in causing target protein mislocalization.…”
Section: The Grabfp System Can Interfere With Protein Localizationsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with observations made by Berry et al (Berry, Olafsson et al 2016), the GrabFP components were in some cases themselves mislocalized due to interaction with target proteins. This was particularly relevant for GrabFP-A Ext and GrabFP-B Int (Figure 2 Figure Supplement 1H), which were, presumably as a consequence, less efficient in causing target protein mislocalization.…”
Section: The Grabfp System Can Interfere With Protein Localizationsupporting
confidence: 91%
“…Recently, it was reported that tethering of nanobodies to specific cellular compartments can result in protein relocalization (Berry, Olafsson et al 2016). In line with these observations, expression of the GrabFP constructs altered the subcellular localization along the apicalbasal axis of the 15 different GFP-tagged cytosolic or transmembrane proteins we tested.…”
Section: The Grabfp System Can Interfere With Protein Localizationsupporting
confidence: 82%
See 1 more Smart Citation
“… Abstract The yeast centrosome or Spindle Pole Body (SPB) is situated in the nuclear membrane, where it nucleates spindle microtubules and acts as a signalling hub. Previously, we used Synthetic Physical Interactions to map the regions of the cell that are sensitive to forced relocalization of proteins across the proteome [Berry et al, 2016]. Here, we expand on this work to show that the SPB, in particular, is sensitive to the relocalization of many proteins.…”
mentioning
confidence: 75%
“…Proteome-wide SPI screens have been used in the past to probe the regulation of the kinetochore [Ólafsson and Thorpe, 2015, 2016] and a set of 23 SPI screens was used to generate a cell-wide map of proteins sensitive to relocalization [Berry et al, 2016]. Relative to the screens of Berry et al our analysis shows that the SPB is particularly sensitive to forcible relocalization.…”
Section: Introductionmentioning
confidence: 99%